Construction of targeted 10B delivery agents and their uptake in gastric and pancreatic cancer cells - Wang, Song; Zhang, Zhengchao; Miao, Lele; Zhang, Jiaxing; Tang, Futian; Teng, Muzhou; Li, Yumin (Frontiers in Oncology, 2023)
Boron Neutron Capture Therapy (BNCT) is a new binary radiation therapy for tumor tissue, which kills tumor cells with neutron capture reaction. Boron neutron capture therapy has become a technical means for glioma, melanoma， and other diseases has been included in the clinical backup program. However, BNCT is faced with the key problem of developing and innovating more efficient boron delivery agents to solve the targeting and selectivity. We constructed a tyrosine kinase inhibitor-L-p-boronophenylalanine (TKI-BPA) molecule, aiming to improve the selectivity of boron delivery agents by conjugating targeted drugs while increasing the molecular solubility by adding hydrophilic groups. It shows excellent selectivity in differential uptake of cells, and its solubility is more than 6 times higher than BPA, leading to the saving of boron delivery agents. This modification method is effective for improving the efficiency of the boron delivery agent and is expected to become a potential alternative with high clinical application value.